Maintenance manager's standard manual - Westerkamp, Thomas A. (BNi Publications, Inc., 2013)
Whether you are a facilities manager, engineer, property owner, developer, or anyone else responsible for maintenance operations, this book is a must-have reference. Not only does it give you all of the essential ingredients for understanding and carrying out successful day-to-day management of maintenance activities, it provides you with an integrated plan for continuous improvement of the maintenance function. It covers structural maintenance, mechanical maintenance, electrical maintenance and instrument repair, maintenance of roads and grounds, power plan maintenance, as well as housekeeping, waste management, air and water quality, and safety. For each of these areas the Manual covers materials planning, preventative maintenance, emergency maintenance, budgeting and expense forecasting, and much more. It even provides you with a complete set of model policies and procedures you can easily edit and adapt for your own organization. What's more, Maintenance Manager's Standard Manual provides a wealth of computerized maintenance management system (CMMS) tips and techniques to help you gain greater control of your IT infrastructure, plus a detailed look at the new capabilities added to the CMMS to better integrate it with day-to-day shop floor control and performance management. --